2018 AIAA Aerospace Sciences Meeting 2018
DOI: 10.2514/6.2018-1102
|View full text |Cite
|
Sign up to set email alerts
|

Grid Convergence for Three Dimensional Benchmark Turbulent Flows

Abstract: Grid convergence studies are performed to establish reference solutions for benchmark three dimensional turbulent flows in support of the ongoing turbulence model verification and validation effort at the Turbulence Modeling Resource website curated by NASA. The benchmark cases are a subsonic flow around a hemisphere cylinder and a transonic flow around the ONERA M6 wing with a sharp trailing edge. The study applies widely-used computational fluid dynamics codes developed and supported at the NASA Langley Rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 48 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…Strategic and 96% wing span. Experimental data from [39], CFL3D, FUN3D, and USM3D data from [38] alteration of the outer FF nacelle surface geometry can, however, efficiently alleviate the effect.…”
Section: Study Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategic and 96% wing span. Experimental data from [39], CFL3D, FUN3D, and USM3D data from [38] alteration of the outer FF nacelle surface geometry can, however, efficiently alleviate the effect.…”
Section: Study Resultsmentioning
confidence: 99%
“…For the validation, the mesh provided by the CFL3D Test/ Validation archive is used [36]. Freestream conditions corresponding to case 2308 of the Onera S2MA wind tunnel test are provided by NASA Langley Research Center Turbulence Model Numerical Analysis [37] and documented in [38] (see Table 2). Experimental results for the pressure distribution are documented for the original wind tunnel tests in [39].…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistics of grids from families 2 (tet), 4 (prism/hex), and 5 (struct) are shown in Table 3. Theses grids are used to compute the reference solutions in the accompanying paper [15].…”
Section: Grid Characteristicsmentioning
confidence: 99%
“…The codes generate families of high-quality consistently refined grids with different elements. These grids are used to establish reference solutions through a grid convergence study reported in an accompanying paper [15].…”
Section: Introductionmentioning
confidence: 99%